Flt3(+) macrophage precursors commit sequentially to osteoclasts, dendritic cells and microglia - Servet-Delprat, Christine (BioMed Central, 2002)
BACKGROUND: Macrophages, osteoclasts, dendritic cells, and microglia are highly specialized cells that belong to the mononuclear phagocyte system. Functional and phenotypic heterogeneity within the mononuclear phagocyte system may reveal differentiation plasticity of a common progenitor, but developmental pathways leading to such diversity are still unclear. RESULTS: Mouse bone marrow cells were expanded in vitro in the presence of Flt3-ligand (FL), yielding high numbers of non-adherent cells exhibiting immature monocyte characteristics. Cells expanded for 6 days, 8 days, or 11 days (day 6-FL, day 8-FL, and day 11-FL cells, respectively) exhibited constitutive potential towards macrophage differentiation. In contrast, they showed time-dependent potential towards osteoclast, dendritic, and microglia differentiation that was detected in day 6-, day 8-, and day 11-FL cells, in response to M-CSF and receptor activator of NFκB ligand (RANKL), granulocyte-macrophage colony stimulating-factor (GM-CSF) and tumor necrosis factor-α (TNFα), and glial cell-conditioned medium (GCCM), respectively. Analysis of cell proliferation using the vital dye CFSE revealed homogenous growth in FL-stimulated cultures of bone marrow cells, demonstrating that changes in differential potential did not result from sequential outgrowth of specific precursors. CONCLUSIONS: We propose that macrophages, osteoclasts, dendritic cells, and microglia may arise from expansion of common progenitors undergoing sequential differentiation commitment. This study also emphasizes differentiation plasticity within the mononuclear phagocyte system. Furthermore, selective massive cell production, as shown here, would greatly facilitate investigation of the clinical potential of dendritic cells and microglia.